Trademark Law - Grynberg, Michael (Open textbook library., 2022)
Welcome to trademark law. This introductory chapter has three purposes. First, it outlines some basics of trademark law at a very high level of generality. Second, it outlines some traditional arguments for the protection of trademark rights. Finally, it introduces some issues that complicate the development and application of trademark law.